TINJAUAN YURIDIS PELAKSANAAN PERWALIAN TERHADAP ANAK DIBAWAH UMUR KORBAN TSUNAMI DI ACEH - YUDHI MARZA HARCA (PREMISE LAW JURNAL, 2014)
ABSTRACT Guardianship is very important for the viability of children (young children) or children who cannot take care of themselves, such as displaced children who are not able to take care of their property or their own environment. In other words, they have not yet been able to act legally; therefore, someone or a group of people are needed to take care of and guide them as guardians for the sake of their safety, their survival, and their property. Guardianship is an institution which attempts to take care of young children’s interest, either their personal interest or their property. A guardian is responsible for children’s welfare and for taking care of their property. A guardian can be sued by the children’s families or by the children themselves when he harms them. Although there is a regulation on guardianship, it has been ignored after the incident of tsunami so that there are many legal problems which cannot be solved. Specifically, Acehnese have simple characters that tend to think and to carry out something which is not difficult and complicated. Since they lack of understanding about guardianship, and the lack of control by the parties or the guardianship institutions that have the right to become the guardian/supervisor, and the lack of coordination among the institutions, the guardianship of children, either its management or its supervision, at Gampong (villages) cannot be controlled effectively. Keywords: Guardianship, Young Children, Tsunami Victims